DIAGNOSIS OF CHIASMAL NEOPLASMS - M. A. Kutin (Opuholi Golovy i Šei, 2015)
Chiasmal neoplasms are a rather common pathology that constitutes as high as 25 % of all cranial tumors. The paper gives the clinical picture of the disease, describes the diagnostic methods for chiasmal neoplasms, which are required to detect the pathology until its evident symptoms appear